1996
DOI: 10.3109/00365529609036890
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Analysis of Symptoms of Non-Ulcer Dyspepsia as Related to Age, Pathology, andHelicobacterInfection

Abstract: Age was the most important determinant of dyspeptic symptoms, but not pathology or Helicobacter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Previously, antrum-predominant gastritis has been strongly linked to peptic ulcer disease (8,9), and in some reports ulcer-like symptoms have been linked to H. pyloripositive functional dyspepsia (13)(14)(15). The nding in our study concerning the best long-term treatment response after successful H. pylori eradication in patients with antrum-predominant gastritis has similarities to peptic ulcer disease.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Previously, antrum-predominant gastritis has been strongly linked to peptic ulcer disease (8,9), and in some reports ulcer-like symptoms have been linked to H. pyloripositive functional dyspepsia (13)(14)(15). The nding in our study concerning the best long-term treatment response after successful H. pylori eradication in patients with antrum-predominant gastritis has similarities to peptic ulcer disease.…”
Section: Discussionsupporting
confidence: 58%
“…pylori infection is a lifelong disease with different topographic subtypes of chronic gastritis. In addition, the 'ulcer-like' symptom subgroup has been associated with H. pylori-positive functional dyspepsia by some investigators (13)(14)(15). Our hypothesis was that these subtypes of chronic gastritis also have a role in the H. pylori eradication response of functional dyspepsia.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These observations are consistent with those reported previously for other ethnic populations. [17][18][19] Moreover, the severity of symptoms had little correlation with the HP status of patients. Other investigators have reported similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…It studied the unconfounded effects of age, pathology, and Helicobacter. It was concluded that age was the most important determinant of dyspeptic symptoms, but not pathology or Helicobacter [7]. Computer-aided capsule endoscopy images evaluation based on color.…”
Section: Literature Reviewmentioning
confidence: 99%